Nanostructured Solar Cell Performance in Relation to the Anodic Aluminum Oxide Membrane: Effects of Anodic Aluminum Oxide Membrane on Nanostructured Solar Cell Performance (Journal of Advances and Scholarly Researches in Allied Education, 2023)
To illustrate how the host anodized aluminum oxide (AAO) membrane influences deviceperformance, three different nanowire solar cell designs have been constructed. The comparabletransmittance spectra amongst the three arrangements suggest that the AAO membrane has very lowoptical absorption. The device's power conversion efficiency (PCE) is investigated, and compared acrosscell topologies with and without an AAO membrane, as a function of carrier transit and collection.Nanowire solar cells can stand on their own and have a PCE of 9.9. PCE is increased to 11.1-11.3 byincluding AAO into the solar cell structure, which reduces interface defects and traps brought on byhumidity and oxygen, and stops CdTe tentacles from coming into direct touch with SnO2 and formingmicro shunt shorts. Partially embedded nanowire solar cells are a desirable construction because theycreate a high number of carriers in the axial direction and a relatively low number of carriers in the lateraldirection, mitigating the effects of non-ideal and non-uniform nanowire development. As a result, theincorporation of an AAO membrane into the design of a solar cell results in improved electro-optical andmechanical characteristics.